Effects of bentonite content on the corrosion evolution of low carbon steel in simulated geological disposal environment. (10th March 2021) - Wei, Xin; Dong, Junhua; Chen, Nan; Yadav, Amar Prasad; Ren, Qiying; Wei, Jie; Wang, Changgang; Ma, Rongyao; Ke, Wei
Highlights: The attached bentonite layer could restrain the cathodic oxygen reduction by virtue of its barrier effect on blocking the diffusion of oxygen. The barrier performance of bentonite could be deteriorated by iron corrosion products, which further accelerated the steel corrosion. New equivalent circuits were proposed to describe the effects of bentonite content on the cathodic and anodic process of steel corrosion. Effects of bentonite content on the corrosion mechanism of low carbon steel in the long-term immersion have been discussed. Abstract: The effects of bentonite content on the corrosion behavior of low carbon steel in 5 mM NaHCO3 + 1 mM NaCl + 1 mM Na2 SO4 solution were investigated by electrochemical measurements combined with X-ray diffraction (XRD) and scanning electron microscopy (SEM). In the initial immersion stage, the cathodic process of low carbon steel corrosion was dominated by the reduction of dissolved oxygen, while it transformed to the reduction of ferric corrosion products with the immersion time. The presence of bentonite colloids could suppress the cathodic reduction of oxygen due to their barrier effect on the diffusion of oxygen. However, the barrier performance of bentonite layer was gradually deteriorated due to the coagulation and separation of bentonite colloids caused by the charge neutralization of iron corrosion products dissolved from the steel substrate. More bentonite colloids could maintain the barrier effect for a long time before it was deteriorated by the accumulation of corrosion products. Conversely, it could lose the performance completely, and the corrosion behavior of low carbon steel reverted to the same as that in the blank solution.